METHOD FOR DETERMINING BTX (BENZENA, TOLUENA, AND XILENE) USING GAS-FID CHROMATOGRAPHY (FLAME IONIZATION DETECTOR) - Silvia Yolanda Kristi (PETRO: Jurnal Ilmiah Teknik Perminyakan, 2021)
At present, the petrochemical industry is growing rapidly. Products from the petrochemical industry are produced from petroleum or natural gas which produces various compounds such as BTX (Benzene, Toluene, and Xylene). BTX is such a poisonous aromatic compound that the International Cancer Research Agency classifies benzene as carcinogenic to humans and other BTX species have a variety of detrimental health effects even at low concentrations. Thus the separation of benzene, toluene and xylene compounds is very important. The analysis technique that is commonly used to determine the BTX compound is gas chromatography, which in this case uses GC-FID. The results shown by this instrument show that all the data obtained meet the acceptance requirements with the test parameters performed.